Evaluation of the service (e-SUS - AB) from the perspective of municipal health managers in the 7th Paraibana Region (Research, Society and Development, 2020)
In order to increase the quality of information management, the Ministry of Health launched the Basic Care Health Information System (SISAB), which is implemented through the e-SUS Basic Care strategy (e-SUS-AB), through Ordinance 1412 of July 13, 2013. The objective of this article was to evaluate the e-SUS - AB service from the perspective of the Municipal Health Managers of the Pianco Valley, how it has facilitated the development of activities and decision-making of Municipal Health Managers through the reports generated by the System. The methodology used was the Grounded Theory (GT), a qualitative method of elaborating a theory based on empirical data from a social reality. Faced with the analysis, it was possible to understand how the regional health managers use the e-SUS - AB reports and how the information produced influence the decision-making process. It was possible to evaluate that the strategy is indispensable for management activities, but some factors still compromise the work.